Life Support Vs Life Cost: Ethical Conflicts in Critical Care Decision Making-A Case Report - Nunik Wijayanti; Hersinta Retno Martani; Ninuk Dian Kurniawati (Indonesian Journal of Global Health Research, 2025)
This case study describe patient receiving treatment in the ICU requested leave against medical advice (LAMA) due to financial limitation regarding hospital bills. This situation presents an ethical dilemma, as the patient requires emergency surgery and mechanical ventilation, making it unfeasible to discontinue the procedure. This study aims to highlight the strategic role of ICU nurses in mediating discharge requests, while upholding patient safety and respecting the family's values and decisions. A man after a traffic accident with a diagnosis of multiple skull fractures and Epidural Hematom (EDH). The patient’s family has provided written informed consent for this case report.This case has been documented in accordance with the CARE Case Report Guidelines. Following the nurse communicated with the case manager and a family conference was held with the medical team, the family decided to agree to surgery on the patient and the costs would be discussed with the extended family. Nurses not only play an active role as coordinators or mediators in providing patient care but also must identify potential financial resources available to the patient's family. This is done to prioritize the patient's interests.